Permeability of steel fibre reinforced concrete - Singh A.P.; Agrawal R.; Singhal D. (My University, 2025)
The investigation reported in this paper was carried out to study the permeability of steel fibre reinforced concrete (SFRC) with varied fibre content. Plain steel fibres were used and the fibre content varied as 0.0%, 1.0%, 2.0% and 4.0%. Efforts were simultaneously, made to correlate the permeability with compressive and tensile strengths. Permeability was observed to decrease significantly with the addition of fibres and it continued to decrease with the increase in fibre content. Linear relationship was observed between permeability and compressive and tensile strengths for plain cement concrete (PCC) as well as SFRC. The relationship suggested for determination of coefficient of permeability through fibre content and compressive strength was found to be in good agreement with the experimental values.